2019
DOI: 10.4317/jced.55913
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of frictional resistance between passive self-ligating brackets and slide-type low-friction ligature brackets during the alignment and leveling stage

Abstract: Background: to compare the frictional resistance between passive self-ligating brackets and conventional brackets with low-friction ligature under bracket/archwire and root/bone interface during dental alignment and leveling. Material and Methods: a tridimensional model of the maxilla and teeth of a patient treated with conventional brackets, and slide ligatures was generated employing the SolidWorks modeling software. SmartClip self-ligating brackets and Logic Line conventional brackets were assembled with sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…The more rigid (or less compressible) the clip material, the higher the friction force produced. [12] This theory supports the results of this study that is the bracket clip of In-Ovation R, which has Co-Cr material, produced higher friction coefficient than Empower and BioQuick, which have stainless steel as their main material.…”
Section: Discussionsupporting
confidence: 88%
“…The more rigid (or less compressible) the clip material, the higher the friction force produced. [12] This theory supports the results of this study that is the bracket clip of In-Ovation R, which has Co-Cr material, produced higher friction coefficient than Empower and BioQuick, which have stainless steel as their main material.…”
Section: Discussionsupporting
confidence: 88%
“…It has been found that the friction of materials with an apparently smooth surface tends to be high if production-related burrs protrude into the slot [ 16 ] or if the archwires show structural irregularities [ 20 ]. Thus, the geometry of irregularities of wire surfaces should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…The friction is less than that of NiTi and that of β‑Ti [ 16 ]. β‑Ti displays a distinct surface roughness [ 20 ], and frictional values are correspondingly high [ 16 ]—up to six times higher than that of stainless steel wires [ 15 ]. Scanning electron microscope (SEM) images of the surface structures of Gummetal®, stainless steel, β‑Ti, CoCr, and NiTi are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Esto hace que sea difícil comparar los resultados observados en el presente estudio. Además, si se trata de investigaciones "in vitro," es difícil garantizar las mismas condiciones en cada uno de los experimentos, incluyendo la posición específica del alambre con respecto a las paredes de la ranura del bracket y que esta posición sea reproducible en cada deslizamiento, aumentando la susceptibilidad a sesgos (13)(14)(15)(16). Todo lo anterior, dificulta contrastar detalladamente los resultados de este estudio con referentes ya publicados.…”
Section: Discussionunclassified